Concept for a Hydrometallurgical Processing of a Copper‐Cobalt‐Nickel Alloy Made from Manganese Nodules. Issue 4 (11th March 2020) - Keber, Sebastian; Brückner, Lisa; Elwert, Tobias; Kuhn, Thomas
Abstract: The processing of manganese nodules for the production of raw materials has been a subject of research for many decades. The nodules contain many valuable metals like copper, cobalt and nickel. In recent years, the German Federal Institute for Geoscience and Natural Resources developed a process for the processing of manganese nodules based on a combined pyro‐ and a hydrometallurgical route. Clausthal University of Technology was assigned to develop the hydrometallurgical process for the treatment of a FeNiCuCo alloy. The developed process consists of pressurized sulfuric acid leaching with the suppression of hydrogen gas formation, precipitation and solvent extraction. Abstract : This article shows the development of a potential processing route for FeNiCuCo alloy produced from manganese nodules. The processing is based on a pressurized sulfuric acid leaching with suppression of hydrogen gas formation followed by precipitations of iron and nickel and solvent extractions for copper and cobalt.